(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Chronic non-specific low-back pain (NSLBP) has become one of the main causes of disability in the adult population around the world. Therapeutic ultrasound is frequently used by physiatrists in the treatment of LBP and is one of the most widely used electro-physical agents in clinical practice. Objective: To see the effects of ultrasound therapy (UST) in the patients with chronic nonspecific low back pain. Methodology: This randomized control trial was performed in the Department of Physical Medicine & Rehabilitation of Dhaka Medical College Hospital during the period from December 2014 to May 2015. Patients presented with chronic nonspecific LBP in an age between 18 and 55 years of both sexes attending in the Department of Physical Medicine & Rehabilitation at Dhaka Medical College Hospital, Dhaka were included as study population. A total of 80 patients presented with chronic nonspecific LBP who had fulfilled the selection criteria were taken as study population. They were divided into two groups named as treatment group (Group A) and control group (Group B). Each group had 40 patients. During follow up 8 patients (4 patients from each group) were lost. Final analysis was done with data collected from 72 patients. Patients of group A were given UST, NSAIDS, exercises and ADL instructions whereas patients of group B were given same treatment except UST. Result: In both groups female were predominant than male. Most of the patients were in 31 – 40 years age group. Mostly housewives suffered from NSLBP. All patients were from either poor or middle-class family. Mean (±SD) duration of pain was 11.3 (±12.5) months and 11.7 (±8.7) months in group A and group B respectively. Sedentary life style and repetitive lifting are the major risk factors in both groups. Character of pain was mostly dull in both groups, severity of pain was mostly moderate and relieving factor was mostly rest in both groups. Prolonged standing and prolonged sitting were the major aggravating factors in both groups. VAS and ODI were reduced gradually in both groups. Conclusion: Ultrasound therapy has a significant role in the management of chronic nonspecific low back pain. Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 122-125